Is Adolescent Employment Still a Risk Factor for High School Dropout?. (20th September 2019) - Staff, Jeremy; Yetter, Alyssa M.; Cundiff, Kelsey; Ramirez, Nayan; Vuolo, Mike; Mortimer, Jeylan T.
Abstract : Past cohorts of teenagers who spent long hours in jobs were more likely to drop out of high school than those who worked moderate hours or did not work at all. This article examines the association between employment intensity and dropout among adolescents in the High School Longitudinal Study of 2009 who traversed high school during a time of decreased prevalence of both employment and dropout relative to earlier cohorts. Analyses reveal that a relatively small percentage of teenagers nowadays are characterized as either intensive workers or dropouts (around 11% each). Yet, despite declines in intensive employment and dropout, disadvantaged youth remain overrepresented in both groups, and intensive work is still a risk factor for poor grades and dropout.